The Southeastern Librarian, Vol.44, No.01, Spring 1994 - Johnson, Theresa; Preuit, Catherine (The Southeastern Library Association, 1994)
The Southeastern Librarian, Vol.44, No.01, Spring 1994. Periodical.
1 electronic record. 48 pages. Scanned from original document. Contents Include - SELA Officers and Staff - cover front, State Library Association Officers - cover back, President’s Page - 3, “When You Come to Learn, Stay to Visit” Dave Fergusson, Guest Editorial - 4. ARTICLES - Academic Architectural Libraries in Alabama: An Introduction by Vinson E. McKenzie - 5, Ten Reasons Why Every Library Should Be Using An Electronic Telephone Directory by Karen Talavera - 9, Library Staff Reallocation: A Humanistic Management Approach by Linda A. Morrissett - 12, Getting Ready for MARC Format Integration by Kathleen L. Wells - 16. DEPARTMENTS - People - 19, Bulletin Board - 22, New & Useful - 24, Stateside - 29, Calendar - 41. SELA ASSOCIATION - Guidelines for SELn Submissions - 2, New Members - 20, Reports from State Reps - 27, SELA Candidates - 34, State Editors - 42, Membership Form - 44.
Keywords: Periodicals | Southeastern Library Association